Assertive Speech Acts in YouTube Comments on the ‘Democratic Candidates Debate Education’ Video - Cantika Khaerunnisa Wijaya; Muhammad Ali Isa Penna; Tatu Siti Rohbiah (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
This research explores how people use assertive speech acts in the comment section of a YouTube video titled “Democratic Candidates Debate: Education,” which was uploaded by ABC News. A qualitative method with content analysis is employed to examine how users share their thoughts, express agreement or disagreement, and participate in online discussions through assertive language. The data were collected from selected comments posted between 2019 and 2020, particularly those reacting to the candidates’ views on education. The analysis applies Searle’s speech act theory, focusing on seven types of assertive speech acts: claiming, stating, reporting, describing, informing, complaining, and concluding. A total of 24 assertive utterances were identified, with the following distribution: claiming (11), reporting (3), complaining (4), stating (2), informing (2), describing (1), and concluding (1). Among these, "claiming" appeared most frequently, indicating that many users shared strong opinions or support, especially for Andrew Yang’s stance on education. Overall, the findings suggest that YouTube serves not only as a platform for viewing content but also as a space where people actively engage in discussions, express their beliefs, and respond to public issues through language.